Responsibility of State for wrongful conviction - Federico Urtubey (Sortuz)
Within the legal system of Argentina, if an individual is confined by preventive detention before trial, it is possible to sue a judicial claim against the State if he or she can prove that such measure was unreasonably prolonged, or if it was illegitimate. This would be a case of jurisdictional responsibility of the State based on prolonged or illegitimate preventive imprisonment. The purpose of this article is to analyze two judicial decisions that resolve claims of this type, trying to shed some light on the argumentative construction developed by the judges when accepting or rejecting the lawsuits. This analysis allows access to the judges' perspectives on the State's jurisdictional activity, the role of criminal justice and the social background of the plaintiffs. The novelty of this approach lies in the fact that other studies on the topic of preventive detention emphasize issues of criminal policy or the functioning of the criminal justice system, while the focus here is on trials involving subsequent financial reparations. Thus, this perspective articulates the fields of legal sociology, law and Discourse Analysis studies.